i-BAKAT: developing holistic student leader / Zulfadli Mahfodz ... [ et al.] - Mahfodz, Zulfadli; Rohayu Ruwati, Ibrahim; Baharudin, Sulyati Akmar; Nur Hisham, Muhammad Shakir Zufayri (Universiti Teknologi MARA, Perak, 2020)
Leadership skills among university students have been developed since they were in school. In the university, there are more opportunities for them to seize and unleash their true talents. Everyone has huge potential to be a future leader. Therefore, a system called i-bakat is introduced as a platform to capture the details of potential students in a database and monitor them systematically. The potential students that we highlighted here are those who have talent in leadership, sport, art, culture and are involved actively in representing their school for certain competitions. We want every student of Universiti Teknologi MARA (UiTM), Perak Branch to be a leader in the class, faculty, or university level. Therefore, in every semester, a selected group of students will be groomed and put them in a structured leadership module that purposely to develop their skills holistically. The leadership skills that are going to be instilled and implemented include language skills, self-confidence, public speaking, organization management and critical thinking skills. For the upper level, students will be challenged by giving specific tasks to execute their ideas and apply all the skills in selected university events. Later, they will be accessed, commented and awarded for their achievement accordingly. This is a comprehensive process which involves a rounded customize module starting from early semester until end of their study period. This initiative is an added value and able to upskill the competency of our graduates. Thus, ensure them to be more prepared and well trained before endeavoring to the real working environment.